2019
DOI: 10.1016/j.bmc.2019.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Profiling withanolide A for therapeutic targets in neurodegenerative diseases

Abstract: To identify new potential therapeutic targets for neurodegenerative diseases, we initiated activity-based protein profiling studies with withanolide A (WitA), a known neuritogenic constituent of Withania somnifera root with unknown mechanism of action. Molecular probes were designed and synthesized, and led to the discovery of the glucocorticoid receptor (GR) as potential target. Molecular modeling calculations using the VirtualToxLab predicted a weak binding affinity of WitA for GR. Neurite outgrowth experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 88 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…Further experiments showed that withanolide A-dependent induction of neurite outgrowth was not achieved by a direct effect on GR, but might be mediated through a closely related pathway, such as ERK, Akt, NF-κB, TRα, or Hsp90. 222 These studies indicate that the efficacy of withanolides on neurons can be utilized to tackle age-related diseases, such as Parkinson's disease and Alzheimer's disease. The glutathione derivative CR-777 ( 320 ) could protect dopaminergic and cortical neurons at nanomolar concentrations, and the observed role of 320 seemed to involve the PI3K/mTOR pathway, indicating that 320 could be considered as a protective agent against a large panel of neuronal stressors.…”
Section: Biological Activities and Mechanismsmentioning
confidence: 99%
“…Further experiments showed that withanolide A-dependent induction of neurite outgrowth was not achieved by a direct effect on GR, but might be mediated through a closely related pathway, such as ERK, Akt, NF-κB, TRα, or Hsp90. 222 These studies indicate that the efficacy of withanolides on neurons can be utilized to tackle age-related diseases, such as Parkinson's disease and Alzheimer's disease. The glutathione derivative CR-777 ( 320 ) could protect dopaminergic and cortical neurons at nanomolar concentrations, and the observed role of 320 seemed to involve the PI3K/mTOR pathway, indicating that 320 could be considered as a protective agent against a large panel of neuronal stressors.…”
Section: Biological Activities and Mechanismsmentioning
confidence: 99%
“…Collectively, the possible mechanism underlying the neuroprotective actions of Withania somnifera could be mediated through several pathways. Several studies have suggested that the protective effect of withanoside IV [119], withanone [120][121][122], withaferin A [123][124][125], and withanolide A [126][127][128][129][130] and other compounds as well as the synergistic action of multiple compounds present in Withania somnifera extract could contribute towards beneficial effect of Withania somnifera in the pathogenesis of neurodegenerative diseases.…”
Section: Withania Somniferamentioning
confidence: 99%
“…Withanolide A increases glutathione biosynthesis in neuronal cells in a corticosteronedependent manner [23]. Profiling of withanolide A for therapeutic targets in neurodegenerative diseases has shown that withanolide A forms several contacts with residues in the glucocorticoid binding pocket but lacks key stabilizing interactions as observed for dexamethasone [45]. More studies are therefore needed to elucidate the possible mechanisms of action of withanolide A, on the glucocorticoid receptor.…”
Section: Discussionmentioning
confidence: 99%